Prototyping high-fidelity multifunctional objects using single-nozzle multi-filament additive manufacturing system with active mixing - Teng Teng; Yefan Zhi; Masoud Akbarzadeh (Materials & Design)
This paper aims to advance the field of additive manufacturing by producing multimaterial objects with intricate topological features and polylithic material distribution through an integrated approach. First, we develop a Single-Nozzle Multi-Filament (SNMF) system equipped with active mixing to blend multiple filaments and deposit a programmable mixture. The system can also deposit gradient transitions between different materials within a single print. Second, we establish a numerical model to represent the material transitional behavior and validated it with experiments. The model enables the precise control of the material transitional interface to ensure high material fidelity. Third, we propose three strategies for designing and modeling multimaterial objects catering to different application scenarios, including image sampling, 2D discrete patches, and 3D surface division. The system’s capabilities were validated through six case studies designed and fabricated through the above approaches for distinct application scenarios, demonstrating the successful materialization of complex designs with multiple functionalities.